The most effective techniques to develop fluency in the speaking skill - Bojórquez Solórzano, Lidia Noemi; García Martínez, Yanky Yohana; Torres Zepeda, Mireya Guadalupe (2024)
This work deals with one particular aspect of the teaching of English as a foreign language: To reach a high level of fluency in the speaking skill, it suggests some of the most effective techniques for teachers of this language to use in order to lead their students to talk in the classroom using the language in a creative, purposeful and individual way. Furthermore, it makes a brief summary of some of the techniques that are less effective than the ones described before. In addition, it will be shown the process that the researchers are going to follow in order to carry out this study, including the different activities that will be developed and the resources that will be used during the research. Besides, each of the steps that plays an important part of the whole research paper will be systematically explained. At the end of the work can be found a classified bibliography whose purpose is to suggest further reading that may assist the teacher in the planning, preparation and implementation of the different techniques in the classroom.